(3fJjLI GdacQ aj EYQGH ChGFd GdShQs - (3YHjO Hf eMeO GdUOjbj GdMeUj GdTGaYj, GHf YJjbs
(3ChdgG (B:s
(3hHYO, ajbhd GdeYQha HGHf YJjb deG cGf YGe JSY hCQHYjf HYO GdCda s
(3BNQgG (B:s
(3bGd GdRQcTj(B: (3hbO PcQJ MceI Pdc aj CSQGQ GdJfRjd, GfJgi hdjcf gPG BNQ eG bUOfG EjQGOg aj gPG GdQbje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B33 - (3U(B46s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B253 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B645s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B623 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B326 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs